Ossifying pleomorphic adenoma presenting as a nasopalatine mass - Bhat, Vikram K.; Shenoy, Supreetha B.; Sangoli, Bhavana (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Pleomorphic adenomas are benign tumors that are uncommon in the nasal cavity. However, they can rarely arise from septum, erode hard palate and thus masquerade a bone tumor. We report one such rare case of septal pleomorphic adenoma with hard palatal extension and ossification. A combined endoscopic intranasal and transpalatal surgical approach was performed and tumor was excised completely. A high index of clinical suspicion and biopsy can diagnose such swellings.